PDF digital watermarking grayscale photocopy detection of printed documents - Soong, Hoong Cheng (2010)
Digital watermarking is a growing research area to mark digital content (image, audio, video,etc.) by embedding information into the content itself. As a result, this technique provides additional and useful features for many application fields. In addition, digital watermarking is also used to provide additional and useful evidences for many application fields especially in copyright infringement detection. For this reason, this research focuses on PDF watermarking and the printed watermarked copy. Apart from the security purpose, it is known that the grayscale photocopied documents are easily duplicated. Therefore, the objective of this research includes identifying the most suitable color that can be used in order to overcome the illegally grayscale photocopied documents. As to get the most suitable color to achieve the objective, a test model is developed to proof that yellow color is suitable to be employed for detecting the duplicated grayscale photocopies easily. Colour theory and colour properties are used to prevent yellow-watermarked authentic stamps that are being photocopied in grayscale, particularly by using luminance concept on the documents to detect illegal grayscale photocopying. The research applies only for grayscale photocopies, as the detection for coloured copies requires disparity techniques for the coloured detection. Based on the disparity techniques, further research if possible, will be conducted for the coloured hardcopied documents.